Medieval Muslim historians and the Franks in the Levant
1 online resource.
Keywords: In Medieval Muslim Historians and the Franks in the Levant seven leading scholars examine the historical writings of seven medieval Muslim historians whose works provide the core chronographical texts for reconstructing the events of the crusading period, 1097-1291. Each chapter examines the life of and influences on each historian, their overall writings, and their historical works related to the Crusades. Each historical text is examined for the current state of modern research, the sources and working method of the author, and its use and relevance for crusader studies and other fields of research. This volume will be of use to anyone studying the events of the Crusades, of Islamic History, or of Arabic Historiography in the medieval period. Contributors include: Frédéric Bauden, Niall Christie, Anne-Marie Eddé, Konrad Hirschler, Alex Mallett, and Françoise Micheau, Lutz Richter-Bernburg